Ophthalmological manifestations in segmental neurofibromatosis type 1. Issue 11 (15th October 2004) - Ruggieri, M; Pavone, P; Polizzi, A; Pietro, M Di; Scuderi, A; Gabriele, A; Spalice, A; Iannetti, P
Abstract : Aims: To study the ophthalmological manifestations in individuals with the typical features of neurofibromatosis type 1 (NF1) circumscribed to one or more body segments, usually referred to as segmental NF1. Methods: Visual acuity and colour tests, visual field examination, slit lamp biomicroscopy of the anterior segment, and a detailed examination of the retina by indirect ophthalmoscopy were performed at diagnosis and follow up in 72 consecutive subjects (29 males, 43 females; aged 1–64 years; mean age 14.6 years) seen at the university departments of paediatrics in Catania and Rome, Italy, during years 1990–2003, who had in restricted body areas: (1) typical pigmentary manifestations of NF1 (café au lait spots and freckling) only (n = 48); (2) NF1 pigmentary manifestations and neurofibromas alone (n = 2); (3) neurofibromas only (n = 15); and (4) plexiform neurofibromas only (n = 7). Results: None of the 72 patients had Lisch nodules in the iris irrespective of age at eye examination or hypertelorism (a "minor" NF1 feature) and none developed typical associated ophthalmological NF1 complications. An additional child had an isolated optic pathways glioma (OPG), which behaved both biologically and radiographically as an NF1 associated OPG. Conclusions: This represents the first systematic study reporting on eye involvement in the largest series of individuals at different ages having segmental NF1. As one of the postulated mechanisms to explain segmental NF1 is somatic mosaicism for the NF1 gene (so far demonstrated only in two patients) the present findings could be explained either by the fact that the eye is too far from the mutated area with NF1 lesions in most cases or by the NF1 (or other "predisposing" or "cooperating") gene mutation restricted to too few cellular clones or to tissues embryologically different from the eye.